Duluth incline base station (Minnesota Streetcar Museum, 1908)
cc6b748409497dd4219a9023d37b26bc
This is the Superior Street base station of the incline, which was located in the vacant right of way of 7th Avenue W. From 1901 to 1911, the incline ran with a single car, instead of two before and after that period.
Minnesota
St. Louis
Central Hillside
Duluth
Mode of access: Internet.
Keywords: Duluth; streetcars; street scene; Transportation